Evaluation of training programmes - An application of Kirkpatrick’s model - De, H K; Saha, G S; Mahapatra, A S; Shasani, S; Panda, N (Journal of the Inland Fisheries Society of India, 2021)
In a bid to build capacity of stakeholders the ICAR-CIFA organises several training programmes each year. State department officials, academicians, progressive farmers and farm women benefit from these programmes. An attempt was made to evaluate the training programmes using Kirkpatrick’s four level model. A composite training index was developed. Data were collected using Googleform with three components - socio-personal details; effectiveness of training and professional relevance of training. The training programs received a composite rating of 84.31%, which reflects the quality of performance of training activities carried out by the Institute. Key words Training; Kirkpatrick’s Level;Evaluation